Exploring New Paradigms in Auditing: Challenges and Opportunities in the Digital Era - Tahir, Arlan (PT. Hafasy Dwi Nawasena, 2024)
Auditing in the digital age has faced significant transformation, giving rise to a new paradigm that brings challenges and opportunities for audit practitioners. The method used in this research is qualitative research that aims to explore new perspectives in audit practice with a focus on accounting, by conducting a comprehensive literature review of recent publications in related academic journals, as well as current research reports in audit and accounting practice. The result of the study is that in the face of increasing complexity and volume of data, the use of technology and sophisticated data analysis is key in improving the efficiency, accuracy, and relevance of the audit process. However, adapting to rapid technological developments, data security issues, and maintaining audit quality remain challenges that need to be overcome. On the other hand, digital solutions enable better collaboration between auditors and clients, respond more quickly to business changes, and provide greater value-added services. Thus, the new paradigm in auditing presents significant challenges, but also opportunities to improve audit practices to be more effective, relevant, and adaptive in the changing digital era.